ISOLASI DAN IDENTIFIKASI SENYAWA KIMIA SERTA UJI AKTIVITAS ANTICANDIDAISIS SERBUK DAUN SIRIH DUDUK (Piper sarmentosum Roxb. Ex Hunter) - Suwandri Suwandri; Hartiwi Diastuti (Universitas Jenderal Soedirman, 2006)
Sirih duduk or Piper sarmentosum Roxb. ex Hunter have been long used the people in Indonesia for traditional medicine to cure various diseases. One of them was used to treat fungoid diseases. This research was aimed to examine the anticandidaisis activity from extract of P. sarmentosum leaves and to isolate and identify the anticandidaisis compounds from P. sarmentosum leaves. The isolation bioactive compounds of P. sarmentosumleaves was performed by extraction the powder of P. sarmentosum leaves using methanol and the bioactivity tests were performed against Candida albicans. The methanol extracts was then fractionated using organic solvents such as n-hexane, benzene, chloroform, and ethyl acetate. Identification of the bioactive compounds was carried out using ultraviolet-visible spectrometry, fourier transform infra red spectrometry and gas chromatography-mass spectrometry. The result showed that the chloroform fraction of methanol extract of P. sarmentosum leaves have activity against C. albicans. The fractionation was performed by coloumn chromatography using n-hexane-ethyl acetate(1:1) eluent. A bioactive compound of sinamic acid derivative was 4-ethoxy-2-hidroxy-3,5-dimethoxy sinamic acid could be purely isolated.